L-shaped association between the blood pressure response index and short-term mortality in intensive care patients with sepsis: An analysis based on the MIMIC-IV database - Heping Xu; Ruiyong Mo; Yiqiao Liu; Huan Niu; Xiongwei Cai; Ping He (PLoS ONE, 2025)
Background Septic shock is a life-threatening condition that requires rapid assessment to reduce mortality. This study investigated the relationship between the blood pressure response index at admission and short-term mortality in septic shock patients. Methods We retrospectively analyzed clinical data from the MIMIC-IV database via multivariable logistic regression, sensitivity analysis, and restricted cubic spline models to explore the associations between the BPRI at ICU admission and short-term mortality. Kaplan-Meier estimates and ROC curves evaluated BPRI’s predictive value. Results In 7,382 patients, a higher BPRI was linked to reduced short-term mortality. Each standard deviation increase in the BPRI led to 2.5%, 2.0%, and 1.8% reductions in in-hospital, 28-day, and 90-day mortality, respectively. K‒M analysis revealed significantly lower short-term mortality in patients with higher BPRIs (P < 0.0001). An L-shaped nonlinear relationship between the BPRI and mortality was observed in the RCS model. The ROC curve for the BPRI showed an AUC of 0.640. Sensitivity analyses revealed an association even after patients with myocardial infarction, malignant cancer, or missing data were excluded. Conclusion An elevated BPRI at ICU admission is significantly associated with reduced short-term mortality in septic shock patients, indicating its potential as an early prognostic tool for risk assessment.